Modal testing : a practitioner's guide - Avitabile, Peter, 1952- (John Wiley & Sons Ltd : The Society for Experimental Mechanics, 2018)
Taking a hands-on approach, this practical, clear, and concise guide explores the issues related to conducting a test from start to finish and covers the cornerstones of the basic information needed while summarizing all the pertinent theory rel.